2022
DOI: 10.3390/agronomy12081856
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transplant Date and Plant Spacing on Biomass Production for Floral Hemp (Cannabis sativa L.)

Abstract: Floral hemp cultivated for the extraction of cannabinoids is a new crop in the United States, and agronomic recommendations are scarce. The objective of this study was to understand the effects of plant spacing and transplant date on floral hemp growth and biomass production. Field trials were conducted in North Carolina in 2020 and 2021 with the floral hemp cultivar BaOx. Transplant date treatments occurred every two weeks from 11 May to 7 July (±1 d). Plant spacing treatments were 0.91, 1.22, 1.52, and 1.83 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…In that study, the increased plant size corresponded to increased floral yields. It should be noted that the earliest planting in the present study occurred $1 month earlier than in the North Carolina trial (Linder et al 2022). The cooler growing conditions during the earlier planting period in the present study may have resulted in smaller differences in total plant growth among the different planting dates compared with the North Carolina study.…”
Section: Resultscontrasting
confidence: 44%
See 3 more Smart Citations
“…In that study, the increased plant size corresponded to increased floral yields. It should be noted that the earliest planting in the present study occurred $1 month earlier than in the North Carolina trial (Linder et al 2022). The cooler growing conditions during the earlier planting period in the present study may have resulted in smaller differences in total plant growth among the different planting dates compared with the North Carolina study.…”
Section: Resultscontrasting
confidence: 44%
“…However, the visual increase in plant canopy did not correspond to increases in flower biomass. Linder et al (2022) reported significant increases in height and width of 'BaOx' plants when planted in May compared with June and July. In that study, the increased plant size corresponded to increased floral yields.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Planting date effects on crop growth, physiology, yield, biomass, and seed composition have been documented in several crops (Chiluwal et al., 2018; Mourtzinis et al., 2017; Tsimba et al., 2013). A recent study in industrial hemp also evaluated the planting date effect on its floral biomass (Linder et al., 2022b). However, the effect of planting date on CBD and THC accumulation pattern over crop growing season in CBD‐dominant hemp cultivars is still unknown.…”
Section: Introductionmentioning
confidence: 99%